2021
DOI: 10.3389/fpsyt.2021.708208
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality Presented to a Child and Adolescent Psychiatry Emergency Service: Increasing Rate and Changing Characteristics

Abstract: Background: Children and adolescents who present to child and adolescent psychiatric emergency departments show a variety of reasons for their presentations. Suicidality, in particular suicidal thoughts and suicide attempts, as well as non-suicidal self-injury (NSSI) play a large and important role. In this context, inpatient admissions frequently serve as crisis intervention.Methods: In this study, face-to-face emergency presentations to the emergency department at our Clinic of Child and Adolescent Psychiatr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…6 Over the past decade, there have been sustained increases in ambulance attendances for self-harm among young persons, [7][8][9] and in mental health and suicidal behaviour-related presentations among children and adolescents to EDs. [10][11][12][13][14] It has been highlighted that successful suicide prevention in young people requires a multi-agency approach, 1,15 and linked data relating to suiciderelated contacts with health and emergency services can provide a comprehensive picture of characteristics of those who are at risk of suicide. Data linkage can provide opportunities for detailed examinations of subgroups at risk (e.g.…”
Section: Key Findingsmentioning
confidence: 99%
“…6 Over the past decade, there have been sustained increases in ambulance attendances for self-harm among young persons, [7][8][9] and in mental health and suicidal behaviour-related presentations among children and adolescents to EDs. [10][11][12][13][14] It has been highlighted that successful suicide prevention in young people requires a multi-agency approach, 1,15 and linked data relating to suiciderelated contacts with health and emergency services can provide a comprehensive picture of characteristics of those who are at risk of suicide. Data linkage can provide opportunities for detailed examinations of subgroups at risk (e.g.…”
Section: Key Findingsmentioning
confidence: 99%
“…Self-injurious thoughts and behaviors range from suicidal thoughts and behaviors, including at least some intention to die, to non-suicidal thoughts and behaviors, among them non-suicidal self-injury (NSSI) (4). Recent findings from our emergency department showed a general increase in emergency presentations over the years 2014 to 2018, particularly for suicidal ideation and NSSI as reasons for presentation (3), as previous studies also observed (5,6). NSSI is defined as self-injurious behavior, voluntary, direct injury or damage to body tissue (e.g., self-cutting, self-hitting, pinching, scratching, and biting) without a specific intentional suicidal behavior that is socially unacceptable (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments of child and adolescent psychiatries are frequently consulted by children and adolescents with self-injurious thoughts and behaviors, and often constitute children's first contact to the mental health care system (1)(2)(3). Self-injurious thoughts and behaviors range from suicidal thoughts and behaviors, including at least some intention to die, to non-suicidal thoughts and behaviors, among them non-suicidal self-injury (NSSI) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in half of the crisis patients examined, symptoms leading to crisis intervention had only been present for a few days, whereas the other half stated that the crisis condition had been present for weeks or even chronically [ 4 ]. In recent years, emergency presentation of children and adolescents for mental health reasons has increased, as papers from several nations report [ 2 , 5 , 6 ]. A cohort study of inpatient treatment (regular and emergency admission) at child and adolescent psychiatric hospitals in Germany detected an increase in inpatient treatment [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, every emergency child and adolescent psychiatric presentation needs immediate assessment regardless of whether an inpatient admission for crisis intervention is indicated. A previous study from Germany reported that 47.1% of patients presenting as emergencies were admitted to an inpatient unit [ 6 ]. Caregivers being present at the emergency department increased the likelihood of treatment alternatives for immediate admission if they presented outside of regular working hours [ 11 ].…”
Section: Introductionmentioning
confidence: 99%